Dissociative recombination and rotational transitions of D+2 in collisions with slow electrons. Issue 1 (25th February 2022) - Epée Epée, M D; Motapon, O; Pop, N; Iacob, F; Roueff, E; Schneider, I F; Mezei, J Zs
ABSTRACT: Rate coefficients for dissociative recombination and state-to-state rotational transitions of the D_2^+ ion induced by collisions with very low-energy electrons have been reported following our previous studies on HD + and H_2^+ . The same molecular structure data sets, excitations (N_i^+ → N_f^+=N_i^++2 for N_i^+=0 to 10) and de-excitations (N_i^+→ N_f^+=N_i^+-2, for N_i^+=2 to 10) were used for collision energies ranging from 0.01 meV to 0.3 eV. Isotopic effects for dissociative recombination and rotational transitions of the vibrationally relaxed targets are presented.